2017
DOI: 10.1021/acscatal.7b00845
|View full text |Cite
|
Sign up to set email alerts
|

Early-Stage Deactivation of Platinum-Loaded TiO2 Using In Situ Photodeposition during Photocatalytic Hydrogen Evolution

Abstract: This work unravels a sudden deactivation of Pt/TiO 2 (P25) during the initial stages of photocatalytic H 2 evolution from aqueous solution that, until now, has gone unnoticed, using a unique combination of in situ photodeposition of Pt with an on-line gas detector system. Utilizing a set of techniques, including highresolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), UV-visible diffuse reflectance spectroscopy (DRS-UV-vis), X-ray powder diffraction (XRD), Raman spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 65 publications
8
77
1
Order By: Relevance
“…Note that the initial activity for P25 was considerably higher but had dropped after minutes, leading to the values reported in literature. This recently discovered early‐stage deactivation is supposed to originate from a complex interplay of UV‐induced oxygen vacancies and the Pt cocatalyst active sites, which induces a change in reaction mechanism associated with CO formation . Importantly, a calcination treatment prior to the reaction to anneal oxygen vacancies can minimize this deactivation process, thus highlighting the impact of defects.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the initial activity for P25 was considerably higher but had dropped after minutes, leading to the values reported in literature. This recently discovered early‐stage deactivation is supposed to originate from a complex interplay of UV‐induced oxygen vacancies and the Pt cocatalyst active sites, which induces a change in reaction mechanism associated with CO formation . Importantly, a calcination treatment prior to the reaction to anneal oxygen vacancies can minimize this deactivation process, thus highlighting the impact of defects.…”
Section: Resultsmentioning
confidence: 99%
“…This certainly highlights that post-catalysis-characterization is required to fully describe the composition of a working photocatalyst. Haselmann et al 43 recently reported for Pt-loaded TiO2 an early stage deactivation after ultrasound pre-treatment. The fast deactivation (within approximately one hour of illumination) was primarily observed for composites with low Pt-loading ( Figure 6.3A).…”
Section: Transient Behavior Of Pt and Ni/nio Co-catalysts: Examples Omentioning
confidence: 96%
“…In contrast, some metal oxides (e.g. IrOx, MnOx, and CoOx) [40][41][42][43] and metal hydroxides (e.g. NiOOH, FeOOH) 44,45 often serve as the water oxidation catalysts.…”
Section: Engineering With Co-catalystsmentioning
confidence: 99%
See 2 more Smart Citations